2018
DOI: 10.3389/fmicb.2018.02134
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Dietary Supplements Containing Probiotics, Micronutrients, and Plant Extracts Against Lead Toxicity in Mice

Abstract: Lead (Pb) intoxication is a serious food safety issue, and the development of relevant dietary strategies is an area of ongoing research. In this study, two different dietary supplements were designed and evaluated for their effects against Pb toxicity in mice. Dietary supplement A contained grape seed extract, tea polyphenols and Lactobacillus plantarum CCFM8661, and dietary supplement B contained vitamin C, calcium carbonate, zinc acetate, and L. plantarum CCFM8661. The results showed that both dietary suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…The administration of epigallocatechin gallate attenuated arsenic-induced oxidative damage in the liver of rats [9]. An inhibitory effect of dietary supplement containing a mixture of grape seed extract, tea polyphenols, and probiotics on toxicity of lead to mice has also been reported [10]. A human study with car battery workers found that garlic supplementation significantly reduced signs of occupational chronic lead poisoning such as irritability, headache, and mean systolic blood pressure [11].…”
Section: Introductionmentioning
confidence: 98%
“…The administration of epigallocatechin gallate attenuated arsenic-induced oxidative damage in the liver of rats [9]. An inhibitory effect of dietary supplement containing a mixture of grape seed extract, tea polyphenols, and probiotics on toxicity of lead to mice has also been reported [10]. A human study with car battery workers found that garlic supplementation significantly reduced signs of occupational chronic lead poisoning such as irritability, headache, and mean systolic blood pressure [11].…”
Section: Introductionmentioning
confidence: 98%
“…In December, after the three-month experience with the probiotic yogurt, preprovocative lead was again low risk at 0.7 ug/g creatinine, but post-provocation using a chelating agent, urine lead excretion significantly increased to 17 ug/g creatinine, which is 8.5 times the upper limit, considerably higher than in August and suggesting substantial elimination using both the probiotic yogurt and chelation. These results can be interpreted considering that probiotics, such as those present in the product consumed by the subject, are known to protect against lead toxicity (17) and may enhance lead elimination (18).…”
Section: Leadmentioning
confidence: 88%
“…Post-provocative lead was high at 7.5 ug/g creatinine (reference range: < 2 ug/g creatinine), over three times the upper limit of the reference interval, suggesting the presence of substantial amounts of lead in the subject's body that chelation was helping remove. In December, after the three-month experience with the probiotic yogurt, preprovocative lead was again low risk at 0.7 ug/g creatinine, but post-provocation using a chelating agent, urine lead excretion significantly increased to 17 ug/g creatinine, which is 8.5 times the upper limit, considerably higher than in August and suggesting substantial elimination using both the probiotic yogurt and chelation, Fig 3. These results can be interpreted considering that probiotics, such as those present in the product consumed by the subject, are known to protect against lead toxicity (Zhai et al, 2018) and may enhance lead elimination (Yi et al, 2017).…”
Section: Leadmentioning
confidence: 88%